Reconciling the results of the z ∼ 2 MOSDEF and KBSS-MOSFIRE Surveys. Issue 3 (29th April 2022) - Runco, Jordan N; Reddy, Naveen A; Shapley, Alice E; Steidel, Charles C; Sanders, Ryan L; Strom, Allison L; Coil, Alison L; Kriek, Mariska; Mobasher, Bahram; Pettini, Max; Rudie, Gwen C; Siana, Brian; et al.
ABSTRACT: The combination of the MOSDEF and KBSS-MOSFIRE surveys represents the largest joint investment of Keck/MOSFIRE time to date, with ∼3000 galaxies at 1.4 ≲ z ≲ 3.8, roughly half of which are at z ∼ 2. MOSDEF is photometric- and spectroscopic-redshift selected with a rest-optical magnitude limit, while KBSS-MOSFIRE is primarily selected based on rest-UV colours and a rest-UV magnitude limit. Analysing both surveys in a uniform manner with consistent spectral-energy-distribution (SED) models, we find that the MOSDEF z ∼ 2 targeted sample has higher median M * and redder rest U − V colour than the KBSS-MOSFIRE z ∼ 2 targeted sample, and smaller median SED-based SFR and sSFR (SFR(SED) and sSFR(SED)). Specifically, MOSDEF targeted a larger population of red galaxies with U − V and V − J ≥1.25, while KBSS-MOSFIRE contains more young galaxies with intense star formation. Despite these differences in the z ∼ 2 targeted samples, the subsets of the surveys with multiple emission lines detected and analysed in previous work are much more similar. All median host-galaxy properties with the exception of stellar population age – i.e. M *, SFR(SED), sSFR(SED), A V, and UVJ colours – agree within the uncertainties. Additionally, when uniform emission-line fitting and stellar Balmer absorption correction techniques are applied, there is no significant offset between both samples in the [O iii ]λ5008/H β versus [N ii ]λ6585/H α diagnostic diagram, in contrast to previously reported discrepancies. We can now combine the MOSDEF and KBSS-MOSFIRE surveys to form the largest z ∼ 2 sample with moderate-resolution rest-optical spectra and construct the fundamental scaling relations of star-forming galaxies during this important epoch.